Crystal morphology data for viscosity modelling of fuel slags – Supplementation of spinel phase and validation by crystallisation in entrained flow gasifiers. (1st November 2021) - Schupsky, Jan Peter; Netter, Tobias; Wu, Guixuan; Spliethoff, Hartmut; Müller, Michael
Highlights: Definition of unique spinel crystal morphology based on various crystallised slags. Provision of spinel crystal morphology datasets for viscosity modelling. Provision of crystal morphology datasets for anorthite, olivine, and melilite. Validation of postulated anorthite and spinel crystal morphologies. Comparison of the recent model approach with previous ones. Abstract: Viscosity modelling is crucial to estimate the flow behaviour of slag in gasifiers. However, viscosity modelling of partly crystallised slags cannot yet be performed satisfactorily. This contribution proceeds with a new approach of ascertaining the crystal phase by crystallisation investigations. The characteristic crystal morphology of spinel was defined, based on its crystallographic nature and the results of quenching and confocal laser scanning microscope (CLSM) experiments. Crystal morphology datasets of spinel, anorthite, melilite and olivine phase were provided. The postulated crystal morphologies were validated by investigations of real PiTER and BOOSTER pilot plant gasifier slags to ensure the transferability from recent and previous experiments to industrial applications. Therefore, blends of coal and biomass fuels with diverse compositions from the "Solid Fuel Entrained Flow Gasification Database" were used. It was succeeded to prove that experimental crystal morphology results align well with the crystal shapes from the pilot plant slags and reference data. Accordingly, the recent and previous crystal morphology results can be directly applied to industrial applications. This validation furthermore proves that the crystal morphologies of the investigated phases are characteristic for each phase, independently of the slag composition in which they crystallise in. A literature review concludes that the three most abundant phases: anorthite, melilite and spinel of typical crystallising gasifier slags are covered with the provided morphology datasets. The collection of these datasets represents a crystal morphology database, which can be used to enhance existing viscosity models and apply them for partly crystallised slags in industrial entrained flow gasifiers.